Tortured for Christ - Wurmbrand, Richard (Bartlesville, Okla. : Living Sacrifice Book Co., 2007)
"Months of solitary confinement, years of periodic physical torture, constant suffering from hunger and cold, the anguish of brain-washing and mental cruelty these are the experiences of a Romanian pastor during his fourteen years in Communist prisons. His crime, like that of thousands of others, was his fervent belief in Jesus Christ and his public witness concerning his faith. Meeting in homes, in basements, and in woods sometimes daring to preach in public on street corners these faithful souls persisted in their Christian witness knowing full well the ultimate cost of their actions. This is their story a classic account of courage, tenacious faith, and unbelievable endurance. This history of the Underground Church reflects the continuing struggle in many parts of the world today" -- BACK COVER.
The Russians' avid thirst for Christ -- "Greater love hath no man" -- Ransom and release for work in the West -- Defeating communism with the love of Christ -- The invincible, widespread underground church -- How Christianity is defeating communism -- How Western Christians can help.
First published by Cross Pub. Co., 1967 under the title Tortured for Christ: today's martyred Church.
Includes bibliographical references (p. 167-168).
Keywords: Wurmbrand, Richard; Lutheran Church -- Romania -- Clergy -- Biography; Persecution -- Romania -- History -- 20th century; Political prisoners -- Romania -- Biography; Communism and Christianity -- Romania -- History -- 20th century; Communism and Christianity -- Europe, Eastern -- History -- 20th century; Romania -- Church history -- 20th century; Europe, Eastern -- Church history -- 20th century; Jewish Christians -- Biography